The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1590/s0044-59672012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogia e geoquímica de perfis de solo com Terra Preta Arqueológica de Bom Jesus do Tocantins, sudeste da Amazônia

Abstract: A comparação de dados morfológicos, mineralógicos e químicos de solo com horizontes antrópicos -Terra Preta Arqueológica (TPA) com Argissolos adjacentes permitiu identificar os principais processos responsáveis pela formação da TPA em um sítio arqueológico no Município de Bom Jesus do Tocantins, sudeste do Estado do Pará. A similaridade entre os dados dos horizontes subsuperficiais do solo com TPA e solos adjacentes indica que o horizonte antrópico do solo TPA foi provavelmente desenvolvido a partir de um hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
(10 reference statements)
3
7
0
11
Order By: Relevance
“…The organic matter content in the ABE was higher at all sites compared to the areas of AD, agreeing with the levels of 46.50 mg dm -3 found by Silva et al (2012), but less than those found by Campos et al (2011) Forms of soil organic phosphorus at black earth sites in the Eastern Amazon…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The organic matter content in the ABE was higher at all sites compared to the areas of AD, agreeing with the levels of 46.50 mg dm -3 found by Silva et al (2012), but less than those found by Campos et al (2011) Forms of soil organic phosphorus at black earth sites in the Eastern Amazon…”
Section: Resultssupporting
confidence: 84%
“…Silva et al (2012), characterising the BJ 8 site by attribute, observed an increase from 20 mg dm -3 in the A1 horizon to 50 mg dm -3 in the B2 horizon.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, terras pretas formed in sandier soils tend to have lower chemical fertility, including lower levels of OC, calcium, magnesium, and phosphorus, as well as lower CEC and base saturation. This has been observed in Araracuara, Colombia (Andrade, 1986), in the Brazilian states of Pará (Silva et al, 2012;Souza, 2007;Kern et al, 2015) and Rondônia (Zimpel Neto, 2009), at the Jiquitaia site in Rio Preto da Eva, Amazonas , as well as in horizons described by Smith (1980) and Kämpf et al (2009). This distinction may hence be associated with local environmental factors and the pedogenic process.…”
Section: Terras Pretas: Core Characteristics and Variabilitymentioning
confidence: 66%
“…() have identified sites with A horizons too light to meet archaeological criteria for classification as terra preta , while still presenting abundant archaeological remains and high chemical fertility. Conversely, terras pretas with low chemical fertility also occur at the Caquetá River in Colombia (Andrade, ), in the southeastern region of Pará, and in the states of Amazonas and Rondônia in Brazil (Kern et al., ; Silva et al., ; Zimpel Neto, ). Soil chemical analyses can thus complement field observation of anthropogenic soils.…”
Section: Historical Conceptions Of Terra Preta and Terra Mulatamentioning
confidence: 99%